Empowernment of School Pioneering of Autonomous Category Fund at SMA N 1 Sayung Demak Regency - Soeharfiati, Soeharfiati (2011)
The objectives of this research are (1) to describe the characteristic of budgeting SPOAC fund at SMA Negeri 1 Sayung Kabupaten Demak. (2) to describe characteristic of SPOAC fund releasing at SMA Negeri 1 Sayung Kabupaten Demak. It is qualitative research and uses ethnography design. This research is conducted in SMAN 1 Sayung Kabupaten Demak. The informants of the research are principal and teacher in SMAN 1 Sayung Kabupaten Demak. The method of collecting data use interview, observation, and documentation. Data analysis uses an analysis of data arranged in site. Data validity is consisting of credibility, transferability, dependability, and conformability. The research results show that (1) the budgeting of School Pioneering of Autonomous Category fund in SMA N 1 Sayung is to the determine procedure. Budgeting of School Pioneering of Autonomous Category fund is started from making team of program management of School Pioneering of Autonomous Category fund that has duty to made proposal that consists of budgeting of School Pioneering of Autonomous Category fund. The budgeting of School Pioneering of Autonomous Category fund is addressed to educational officer in Demak which is done in stages that is 2008/2009 academic year, 2009/2010 academic year, and 2010/2011 academic year. The aspects that are considered in making budget are eight education standards that is content standard, SKL standard, process standard, education and education employee standard, facilities standard, management standard, defrayal standard, and evaluation standard. (2) Liquefaction process of School Pioneering of Autonomous Category fund at SMA N 1 Sayung is based on Decree of Principal. Liquefaction process of based on School Pioneering of Autonomous Category fund is started with opening the account in bank that has MoU with educational officer of province. SMA N 1 Sayung opens an account in BNI bank based school name not personal name. The time of liquefaction is done according to the on agreement between educational officers of province with SMA N 1 Sayung. Before the liquefaction of School Pioneering of Autonomous Category fund, the board of program manager prepares the document such as form of liquefaction fund, photocopy of ID card, decree of school board, decree of principal, and decree of treasurer.